Narrativas de desenvolvimento profissional de uma formadora de professores: o caso do Laboratório de Materiais Didáticos de Ensino da Matemática (LAMADEM) da UFCG - Brito, Alexsandra Felix de (2023)
This research is concerned to the works developed by the Group Estudos de Narrativas de Professores em Formação (GENPROF) from the Post-Graduated Program of Education from the Universidade Federal do Rio Grande do Norte, aiming to reflect about the process of formation and professional development in the Laboratory of Didactic Material of Teaching Mathematics (LAMADEM) from the Universidade Federal de Campina Grande (Campus I), trying to understand, to reframe, to rethink and to socialize this formation. This study has based on the theoretical field of Mathematics Education in the perspective of Social History of Mathematics Education (HISOEM), as well as it consists on a Repertory of Theoretical-Conceptual Coordinates of Reference (RCT-CR), proposed by González (2017), related to the Mathematics Education. This study brings reflections related to the formation of teachers, specifically in teaching Mathematics in the Pedagogy curse and knowledge necessary to this formation; as well as related to the Laboratory of Teaching Mathematics proposing questions about the use of didactic materials. This research is qualitative in the Education field, related to the autobiographic narrative category, based on the epistemological approaches presented mainly by Bicudo (2011), González (2020), Nacarato, Passos e Lopes (2019) e Passeggi (2016), focusing on the process of formation in teaching mathematics of the researcher (subject of this own research), assuming as main source of information her academic and professional trajectory in the referred laboratory. In the analytical proceedings of this research, it uses the strategy of archaeological immersion and hermeneutic contemplation (González; Villegas, 2009), based on the phenomenological guidance of Mathematics Education (Bicudo, 1999, 2011), related to the experiences and perceptions of the empirical source, in a polyphonic dialog to the autobiographical narrative (testimonial source) and the Repertory of Theoretical-Conceptual Coordinates of Reference (documental source). As a result, this study points some sense units, significant units and comprehensive interpretation that guide possible understandings and redefinition of a history of professional development in the light of theory and practice relationship. In addition to this, this study contributes to evidence the autobiographical narrative and its importance to the research and historical social interpretations linked to the teacher formation and to the practice of mathematics teaching, once narrative and reflections permit professional and personal self-comprehension, as well as redefinition of the teaching and learning Mathematics process offered in the formation curses of teachers that use or not the alternative of the laboratory of Teaching Mathematics.